Prevalence and Factors Associated With Syphilis in People Living With HIV/AIDS in the State of Pará, Northern Brazil - Pedro Leão Fontes Neto; Ricardo Roberto de Souza Fonseca; Ricardo Roberto de Souza Fonseca; Maria Eduarda de Sousa Avelino; Maria Eduarda de Sousa Avelino; Elizandro Monteiro Vilhena; Maria dos Anjos de Abreu Pina Barbosa; Carmen Andrea Freitas Lopes; Samara Tatielle Monteiro Gomes; Bianca Jorge Sequeira; Rogério Valois Laurentino; Felipe Bonfim Freitas; et al. (Frontiers Media S.A., 2021)
Syphilis continues to be a public health problem worldwide and its incidence has increased in people living with HIV/AIDS in recent years. This study determined the prevalence and factors associated with syphilis in people living with HIV/AIDS in the city of Belém, northern Brazil. A cross-sectional study was conducted from June to November 2018. A total of 500 people living with HIV/AIDS attended at a specialized unit of the public health network of the State of Pará were studied. Questionnaires were used to collect socio-demographic data and potential risk factors for syphilis. Blood samples were collected from all subjects and screened for syphilis using VDRL, and the seropositive were confirmed using FTA-abs. Logistic regressions were used to identify the factors associated with syphilis. Most subjects were male (56.8%), had more than 40 years (54.0%), single (63.0%), had finished high school (54.2%), had monthly income ≤1 minimum wage (72.4%), and had been born to the city of Belém (59.8%). Prevalence of syphilis was 6.4%. Eight characteristics/behaviors associated with syphilis: male, young adults, single, studied at least high school, monthly income >1 minimum wage, homosexual/bisexual, does not use or sporadically use condoms during sexual intercourse, and have had more than one sexual partner in the last three months. The prevalence of syphilis in people living with HIV/AIDS in Belém is low when compared to other Brazilian states. However, there is a need for public policies and actions to monitor, control and prevent these two sexually transmitted infections.